EFEKTIFITAS RENDAM KAKI MENGGUNAKAN AIR HANGAT TERHADAP PENURUNAN TEKANAN DARAH PADA LANSIA DIWILAYAH KERJA PUSKESMAS SIMPANG TIGA KOTA PEKANBARU TAHUN 2016 - yessi harnani (Jurnal Kesehatan Komunitas, 2017)
Hypertension is a heart and blood vessels disease that is manifested by rising blood pressure. Untreated hypertension will lead to complication such as stroke and heart failure. Soak feet warm water is one of the complementary therapy that can reduce blood pressure. The purpose of this research is to ï¬nd out the eï¬€ecveness of soak feet warm water therapy to reduce blood pressure in the elderly. This research was a quantave by using the pre-experimental design and pretest and posest approach. The Sample were elderly with hypertension in working area of Puskesmas Simpang Tiga Pekanbaru. The sampling technique was used purposive sampling. The data collection techniques were used observation and measuring blood pressure by using sphignomanometer. The data analyzed was used Wilcoxon test. The Results showed that generally elderly with hypertension were on stage II. Stasc result showed that mean blood pressure post soak feet warm water therapy was 74,00 and standard deviaon was 5, 026, with the sistolic P value was 0.000 (<0.05) and diastolic P value was 0.000 (<0.05). So, it could be stated that soak feet warm water therapy eï¬€ecve to reduce blood pressure in elderly. It is recommended to elderly with hypertension to always controlling their blood pressure, if there is a rising of blood pressure they could using soak feet warm water therapy to treat hypertension as a complementary therapy, cheap and easy to do indenpendently.